2021
DOI: 10.1016/j.nicl.2021.102819
|View full text |Cite
|
Sign up to set email alerts
|

Altered regional activity and connectivity of functional brain networks in congenital unilateral conductive hearing loss

Abstract: Highlights Focal brain function and seed-based functional connectivity were first analyzed in congenital unilateral CHL. Auditory and visual networks showed altered regional activity and functional connectivity. Abnormally high activity in the left ITG was positively correlated with duration of disease. Higher-order networks including frontoparietal regions and DMN demonstrated abnormal functional connectivity. GSR may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…The inferior frontal gyrus has been implicated in various cognitive processes, including language production and executive functions (Hampshire et al, 2010;Ishkhanyan et al, 2020). Previous studies have reported similar intrinsic brain activity alterations in hearing loss patients (Zhou et al, 2019;Chen et al, 2020;Yang et al, 2021). For instance, Chen et al, (2020) found decreased static ALFF and fALFF in the auditory cortex and visual cortex in unilateral SSHL, and Zhou et al (2019) found abnormal static ALFF in the inferior frontal gyrus in unilateral acute tinnitus patients with hearing loss.…”
Section: Discussionmentioning
confidence: 67%
“…The inferior frontal gyrus has been implicated in various cognitive processes, including language production and executive functions (Hampshire et al, 2010;Ishkhanyan et al, 2020). Previous studies have reported similar intrinsic brain activity alterations in hearing loss patients (Zhou et al, 2019;Chen et al, 2020;Yang et al, 2021). For instance, Chen et al, (2020) found decreased static ALFF and fALFF in the auditory cortex and visual cortex in unilateral SSHL, and Zhou et al (2019) found abnormal static ALFF in the inferior frontal gyrus in unilateral acute tinnitus patients with hearing loss.…”
Section: Discussionmentioning
confidence: 67%
“…A contralateral transmission of the direct sound is also present with medium AC components, but at a lower level. Another possible explanation is a possible deprivation of the auditory pathway attributable to prolonged high-level conductive HL, especially with unusable conventional hearing aids prior to Osia fitting, such as in patients with auditory canal atresia [ 7 , 21 ]. Our results show a negative dependence of speech comprehension with Osia on ABG and thus they differ from those reported by Mylanus et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although children with UCHL tend to have better school performance than those with SNHL, most of them still report communication and behavioral problems and need some sort of resource assistance [ 51 , 52 ]. Recently, a neuroimaging study has revealed abnormally high brain activities in the left inferior temporal gyrus of UCHL patients, which is positively associated with the duration of hearing loss [ 53 ]. This finding demonstrated that even partial hearing deprivations, such as UCHL can cause progressive alterations in functional brain networks.…”
Section: Discussionmentioning
confidence: 99%